Jesus changed my life [compact disc] - Nichole, Katy (Centricity Music, 2023)
The highly anticipated debut album from singer-songwriter Katy Nichole. Her debut single, In Jesus Name (God of Possible), was inspired by words taken from her prayer journal in the midst of a global health crisis, and has become an anthem to many around the world.